2017
DOI: 10.1002/bies.201700126
|View full text |Cite
|
Sign up to set email alerts
|

Linking Mitochondria and Synaptic Transmission: The CB1 Receptor

Abstract: CB1 receptors are functionally present within brain mitochondria (mtCB1), although they are usually considered specifically targeted to plasma membrane. Acute activation of mtCB1 alters mitochondrial ATP generation, synaptic transmission, and memory performance. However, the detailed mechanism linking disrupted mitochondrial metabolism and synaptic transmission is still uncharacterized. CB1 receptors are among the most abundant G protein-coupled receptors in the brain and impact on several processes, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 97 publications
0
37
0
1
Order By: Relevance
“…As one of the most abundant GPCRs in the brain (111), CB 1 receptors are especially important in mediating either physiological and/or pathological stimuli presynaptically, postsynaptically and from within the cell (112114). As described above, pharmacological and genetic isolation of mitochondrial CB 1 receptors have underscored their role in excitatory synaptic transmission as well as in memory performance (77).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most abundant GPCRs in the brain (111), CB 1 receptors are especially important in mediating either physiological and/or pathological stimuli presynaptically, postsynaptically and from within the cell (112114). As described above, pharmacological and genetic isolation of mitochondrial CB 1 receptors have underscored their role in excitatory synaptic transmission as well as in memory performance (77).…”
Section: Introductionmentioning
confidence: 99%
“…The CB 1 -mediated memory impairment appears to be due to decreased protein kinase A (PKA)-dependent phosphorylation of complex I proteins, leading to decreased ATP and decreased mitochondrial respiration. Thus there appears to be a direct link between mitochondrial CB 1 receptors, bioenergetics and higher brain function (114). The exact mechanisms underlying this process are still unclear, but dissecting the specific proteins/pathways involved in this process may generate new therapeutic tools for brain disorders leading to memory loss.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of functional CB1R in brain mitochondria (mtCB1R) made it necessary to revisit the physiological impact of CB1R signaling in brain and to discuss possible downstream effects of mtCB1R activation. In their comprehensive overview Djeungoue‐Petga et al summarize the potential impact of mtCB1R on the regulation of brain physiology. CB1R regulates numerous brain tasks, including synaptic activity, perception and memory performance, and at least some of these functions might be mediated by mtCB1R.…”
mentioning
confidence: 99%
“…It is well established that cannabinoid administration impacts on mitochondrial structure. Djeungoue‐Petga et al hypothesize that mtCB1R activation might have a crucial role in this process, and showed that mtCB1R activation decreases mitochondrial mobility, an outcome that is probably linked to the reduced mitochondrial metabolism. Moreover, activation of mtCB1R decreases flux through the electron transport chain and thus mitochondrial oxygen consumption and energy production, which likely impacts on ATP generation, the production of the central neurotransmitters glutamate and GABA and synaptic transmission.…”
mentioning
confidence: 99%
See 1 more Smart Citation